Kant’s Conception of Conscience - Eldem, Umut (Con-Textos Kantianos. International Journal of Philosophy, 2020)
In this paper I provide a detailed account of Kant’s conception of conscience in order to answer a significant question that has recently arisen in the secondary literature: How should we understand Kant’s insistence on the infallibility of conscience? Some commentators have tried to make sense of the claim by suggesting that conscience is a special kind of moral judgment, while others have argued that it is a kind of feeling. My contention is that neither option is helpful in comprehending why and how Kant develops his ideas about conscience in this specific and peculiar way. I argue that the appropriate way to understand this conception is to establish its broader significance for Kant’s moral philosophy, together with his understanding of human moral agency.